These other answers are perfectly right, but you do not actually have to do substitution to solve this problem!

The derivative of (x+1) = 1, so there is no chain rule leftovers we need to worry about. If there was, then we would have to do some sort of substitution.

We can just do a simple power rule integration.

`int_0^1(x+1)^2003dx` = `[(1/2004)*(x+1)^2004]_0^1`

Then we evaluate.

`(1/2004)*(1 + 1)^2004 - (1/2004)*(0 + 1)^2004`

`(1/2004)*(2)^2004 - (1/2004)*(1)^2004`

`(1/2004)*(2^2004 - 1)`

`(2^2004 - 1)/2004`

The definite integral when evaluated `int_0^1(x+1)^2003dx = (2^2004 - 1)/2004`

You need to evaluate the given definite integral, hence, you need to use integration by substitution, such that:

`x + 1 = t => dx = dt`

You need to change the limits of integration, such that:

`x = 0 => t = 1`

`x = 1 => t = 2`

Replacing the variable and the limits of integration, yields:

`int_1^2 t^2003 dt = (t^2004)/(2004)|_1^2`

You need to use the fundamnetal theorem of calculus, such that:

`int_1^2 t^2003 dt = 1/2004(2^2004 - 1^2004)`

`int_1^2 t^2003 dt = (2^2004 - 1)/2004`

Hence, evaluating the given definite integral, using integration by substitution, yields `int_0^1(x+1)^2003 dx = (2^2004 - 1)/2004` .

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now